2017
DOI: 10.4103/njcp.njcp_340_16
|View full text |Cite
|
Sign up to set email alerts
|

Subdural empyema: Clinical presentations and management options for an uncommon neurosurgical emergency in a developing country

Abstract: BAAD is the near approximated option to standard craniotomy management in a limited resource facility and it has a very good clinical outcome. However, more studies are required to draw the final conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 2 publications
1
18
0
2
Order By: Relevance
“…[ 13 15 16 17 ] In a 10-year review of cases of intracranial SDE in an eastern Nigerian facility, the authors reported a 15.4% positive culture rate. [ 6 ] Our low positive yields from SDE cultures may be attributable to the large percentage of patients administered antibiotic therapy before presentation to tertiary care, a hypothesis that was also alluded to by Chikani et al [ 6 ]…”
Section: Discussionmentioning
confidence: 95%
“…[ 13 15 16 17 ] In a 10-year review of cases of intracranial SDE in an eastern Nigerian facility, the authors reported a 15.4% positive culture rate. [ 6 ] Our low positive yields from SDE cultures may be attributable to the large percentage of patients administered antibiotic therapy before presentation to tertiary care, a hypothesis that was also alluded to by Chikani et al [ 6 ]…”
Section: Discussionmentioning
confidence: 95%
“…(5,2) En cuanto a la etiología infecciosa, coinciden los gérmenes identificados en nuestra revisión con los encontrados en los empiemas secundarios a intervenciones quirúrgicas, siendo el staphylococcus aureus el germen de mayor incidencia. (6,7) El lapso de aparición de los empiemas en nuestra revisión, cuando fueron secundarios a la evacuación de un HSD previo, fue de hasta 3 meses posterior a la cirugía, lo que no está descrito en la literatura revisada, con promedio de un mes posterior a ellas, lo que si se encontró descrito en otras publicaciones. Por tanto, debe considerarse en la aparición de este tipo de complicación relacionada con una cirugía previa de evacuación de un subdural (Figura 3), que puede tener una larga latencia en su debut en los pacientes.…”
Section: Discussionunclassified
“…En relación con lo anterior, una indicación adecuada para el uso de craneotomía serían aquellos casos con presencia de tabicaciones al interior de la colección (1) . Algunos trabajos mencionan que habría menor recidiva cuando se utiliza la craneotomía (7) , sin embargo, en nuestra revisión no se objetivó ninguna diferencia.…”
Section: Discussionunclassified
“… 9 , 25 However, spinal puncture is not advised for the evaluation and diagnosis of SDE, because it can be life threatening to patients with elevated ICP and empyemas, thereby leading to mass effect. 8 , 17 , 26 The mainstay of SDE treatment consists of combined empirical antimicrobial therapy and surgical intervention. 2 , 10 , 22 , 25 , 29 , 32 , 33 Patients are rarely managed solely with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment consists of burr hole aspiration or craniotomy for drainage and debridement of the SDE. 18 , 24 , 26 It is recommended that the collection of pus obtained upon evacuation undergo laboratory evaluation for both aerobic and anaerobic cultures. 13 , 25 , 27 , 32 Antibiotic therapy should be adjusted to account for reported microorganisms from culture results.…”
Section: Discussionmentioning
confidence: 99%